Professional writing skills a write it well guide - Terk, Natasha (Gildan Audio, 2018)
A bestseller since 1990 and fully updated in 2010, Professional Writing Skills: A Write It Well Guide, provides a step-by-step process for planning business letters, memos, e-mail, and other business documents. Learn how to position your message from the reader s point of view, write persuasively, include the right information, and organize the information logically. Expanded sections on language, punctuation, and grammar offer busy professionals the tools they need to get their message across clearly, concisely, and professionally.
Downloadable audio file
Keywords: Business writing -- Handbooks, manuals, etc; Business; Style commercial; Guides, manuels, etc; Affaires; businesses (business enterprises); BUSINESS & ECONOMICS; General; Business writing; Downloadable audio books; Handbooks and manuals; Audiobooks; Livres audio